Habitat modification driven by land use as an environmental filter on the morphological traits of neotropical stream fish fauna - Baldasso, Mara Cristina; de Oliveira, Anielly Galego; Kliemann, Bruna Caroline Kotz [UNESP]; Delariva, Rosilene Luciana (FapUNIFESP (SciELO), 2024)
The ecomorphological attributes of fish are influenced by various factors inherent to their environment, enabling them to serve as indicators of environmental conditions resulting from habitat loss. We evaluated the variation in the ecomorphological characteristics of fish fauna considering the forest cover percentage in streams of the Iguaçu River basin, an ecoregion characterized by high endemism. Environmental variables were measured alongside fish collection by electrofishing with four samples per site. We evaluated 12 ecomorphological indices for 26 species. The combination of environmental variables resulting from forest cover loss and silting led to habitat homogenization, a significant factor in morphological structuring. Streams with lower forest cover showed a prevalence of morphological traits associated with enhanced performance in silted margins, such as caudal fin aspect ratio, dorsal and anal fin relative area, caudal peduncle relative width, pelvic fin aspect ratio. In contrast, the pectoral fin aspect ratio and ventral mouth orientation were traits positively related to the rocky substrate and forest streams. Thus, habitat loss and alteration have imposed selection pressures on species with more specialized traits and habitat use. These findings underscore the critical role of preserving forest cover in maintaining fish diversity.
Keywords: Ecomorphology; Forest cover; Freshwater fish; Habitat loss; Human pressure